2021
DOI: 10.3390/su132212374
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biofuels in Energy Transition, Green Economy and Carbon Neutrality

Abstract: Modern civilization is heavily reliant on petroleum-based fuels to meet the energy demand of the transportation sector. However, burning fossil fuels in engines emits greenhouse gas emissions that harm the environment. Biofuels are commonly regarded as an alternative for sustainable transportation and economic development. Algal-based fuels, solar fuels, e-fuels, and CO2-to-fuels are marketed as next-generation sources that address the shortcomings of first-generation and second-generation biofuels. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 127 publications
(119 reference statements)
0
21
0
Order By: Relevance
“…Macroalgae, on the other hand, have clear potential for the development of biofuels, as reported in previous reports [12,13]. Previous studies have shown seaweed (macroalgae) potentiality as a source of proteins, carbohydrates, minerals, dietary fiber, vitamins, and saturated and unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 54%
“…Macroalgae, on the other hand, have clear potential for the development of biofuels, as reported in previous reports [12,13]. Previous studies have shown seaweed (macroalgae) potentiality as a source of proteins, carbohydrates, minerals, dietary fiber, vitamins, and saturated and unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 54%
“…(1) As the accelerator content increases, the enthalpy increases, the activation energy decreases, and the curing reaction occurs at a lower temperature. (2) The obtained curing kinetic model shows that in the range from 0.5 wt.% to 3 wt.%, as the accelerator content increases, the preexponential factor A decreases, the order of reaction m increases, and n decreases. The value of n is always greater than m, and the curing process can be represented well by the Sestak-Berggren autocatalytic model.…”
Section: Discussionmentioning
confidence: 91%
“…(1) The accelerator attacks the anhydride to generate carboxylate anion, as shown in Figure 4a; (2) The carboxylate anion attacks the epoxy group and opens the epoxy group to generate an oxygen anion, as shown in Figure 4b; (3) Oxygen anions continue to attack other anhydride groups to form carboxylate anions, as shown in Figure 4c. First, the tertiary amine of BDMA reacts with anhydride groups to form carboxylate anions and participates in the curing reaction as a reaction center.…”
Section: Analysis Of Curing Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of everyday processes involving the combustion of fossil fuels for electricity generation as well as transportation have led to a marked rise in the Earth's average surface temperature by causing CO 2 levels in the atmosphere to rise gradually. 1,2 As a result, reducing CO 2 emissions has become urgently necessary for protecting the atmosphere. 3 Carbon dioxide capture and storage (CCS) is regarded as an efficient strategy to curtail CO 2 discharge and hence effectively halt global warming.…”
Section: Introductionmentioning
confidence: 99%